The long haul : a trucker's tales of life on the road - Murphy, Finn, 1958- (W W. Norton & Company, 2017)
A long-haul trucker reflects on the changing realities of the working class as witnessed during journeys ranging from the I-95 Powerland and the Florida Everglades to the truck stops of the Midwest and the Rocky Mountains.